2019
DOI: 10.1055/s-0039-1678552
|View full text |Cite
|
Sign up to set email alerts
|

Apneic Oxygenation for Pediatric Endotracheal Intubation: A Narrative Review

Abstract: Apneic oxygenation (ApOx) has shown to be effective in adult populations in a variety of settings, including prehospital, emergency departments, intensive care units, and elective surgery. This review aims to assess the available literature for ApOx in the pediatric population to determine its effects on hypoxemia, safe apnea times, and flow rates employed safely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Multiple studies from pediatric emergency departments have demonstrated that in combination with other quality improvement measures, routine use of passive oxygenation during endotracheal intubation reduces the incidence of adverse events . Given this evidence together with the known increases in safe apneic times, the PeDI Collaborative, which is the group behind the PeDI‐R, has recommended the use of a difficult airway bundle checklist (Figure ), which includes the use of supplemental oxygen during attempts at tracheal intubation.…”
Section: Oxygen Deliverymentioning
confidence: 99%
“…Multiple studies from pediatric emergency departments have demonstrated that in combination with other quality improvement measures, routine use of passive oxygenation during endotracheal intubation reduces the incidence of adverse events . Given this evidence together with the known increases in safe apneic times, the PeDI Collaborative, which is the group behind the PeDI‐R, has recommended the use of a difficult airway bundle checklist (Figure ), which includes the use of supplemental oxygen during attempts at tracheal intubation.…”
Section: Oxygen Deliverymentioning
confidence: 99%
“…Regarding the profile of patients who are intubated in pediatric emergencies, this is data that varies greatly depending on the center studied [3][4][16][17][18][21][22][23] , and there are few recent studies with an adequate sample. In this review, the study carried out by Céspeez et al 19 identified that the main indication for intubation was cardiopulmonary failure, with this and respiratory failure also being associated with greater difficulty in carrying out the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has increased in popularity over the last ten years due to its ability to reduce desaturation during intubation in the ED and ICU, and in healthy patients undergoing elective surgery in adult studies (8,18,19). This technique has also been implemented in obesity, obstetrics, and pediatrics (16,20). In a small number of pediatric studies in a non-RSII condition, ApOx could prolong safe apneic time and decrease the incidence of hypoxemia (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%